Gossiping as a response to conflict with the boss: alternative conflict management behavior?. Issue 4 (7th October 2014) - A Posthuma, Richard; Dijkstra, Maria; Beersma, Bianca; van Leeuwen, Jelle
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The current paper aims to argue that it is important for conflict management research to start focusing on leader–follower conflict as a "special case" of conflict because the relationship between leaders and followers is, by definition, characterized by divergence of interest and, second, because it is asymmetric in terms of power and vulnerability. Moreover, it is argued that conflict management research should start to examine the various behaviors that people engage in as a response to conflict, in a broader sense, than has been done until now. Research on conflict management increasingly recognizes the significance of interpersonal relations in the workplace. Design/methodology/approach – As a case in point, a survey study among 97 Dutch police officers is presented. Leaders' conflict management behaviors as assessed by followers is measured. In addition, followers' experienced interactional justice and the extent to which they indicated that they would engage in negative and/or positive gossip about their leader was measured. Findings – Results demonstrate that more forcing and avoiding leader conflict management behavior was related to more negative and less positive gossip about leaders. Moreover, more problem-solving and yielding leader conflict management behavior was related to less negative and more positive gossip. All relationships between leader conflict management behavior and follower gossip were mediated by followers' experienced interactional justice. Originality/value – It is hoped that the findings put research on the broader implications of interactional justice in leader–follower interactions, and on gossip, on the research agenda of conflict researchers.